Automatic Control of Electrical Loads Using Human Claps - Das, Papendu; Seth, Abhijit; Das, Aparna; Majumder, Pritha; Mitra, Sayantan; Guha, Manish; Sur, Dibyendu (International Journal of Computer Sciences and Engineering, 2025)
In our day to day modern life, time is a very vital factor for us. In order to save time as much as possible, the concept of clap switch has been introduced in this work. For example, when a person walks from one room to another, it becomes very tiresome and time consuming to move on to the switch board and switch the lights on and off. Therefore an automated human clap controlled system has been implemented and the detailed development of the circuit has been documented in this paper. The method has been implemented by using a sound acquiring device and sound to electrical energy conversion method and the circuit switching connections in order to control the switching on and off of electrical loads.